Strategi Pengelolaan Kelas - Naharuddin Bakri; Usman U; M. Shabir U (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to determine the classroom management strategy. Given that in order to achieve the expected learning objectives, various strategies are certainly needed, one of which is the classroom management strategy. In the classroom, teachers play an important role as the main actor in implementing learning activities. This study is the result of a study or literature review sourced from Library literature or Library materials, both in the form of books and articles published through printed and online scientific journals. The focus of the study in this article is on classroom management strategies that are relevant to Islamic religious education learning. The data obtained are reviewed/analyzed and then presented descriptively in the form of an article. The results of the study show that classroom management strategies are a conscious and planned effort to organize teaching and learning activities systematically which lead to the preparation of facilities and infrastructure and teaching aids, arrangement of learning spaces, realizing situations or conditions for the teaching and learning process so that they run well and achieve the goals set. The conclusion is that classroom management creates an effective and enjoyable teaching and learning atmosphere and can motivate students to learn well.